Democratization in clan-based societies: explaining the Mongolian anomaly. Issue 5 (4th July 2018) - Aagaard Seeberg, Michael
ABSTRACT: Mongolia is a long-standing democratic anomaly – a democracy in a clan-based society – that is rarely discussed in research. This article addresses the question, why did Mongolia and the Central Asian countries embark upon markedly different regime trajectories following 70 years of Soviet rule? I argue that the prospects of democracy were shaped by a complex relationship between clan-based traditional authority structures, social relations based on nomadism and the style of Soviet rule. In Mongolia, Soviet authorities carefully enforced collectivization across kin groups and provided all necessary public goods to citizens, effectively dismantling clan-based authority structures. This process unintendedly fortified nomadic social relations that enabled re-emergent elements of opposition and forces in civil society to fill the void of authority generated by the Soviet collapse and to use this counterweight to state power to push for competitive politics. In contrast, the Soviet authorities' "divide and rule" with clans in Kyrgyzstan reproduced clans that easily took on a dominant role on the eve of the Soviet breakdown and filled the void of authority by placing themselves at the apex of political power providing welfare services and political order. This placed Kyrgyzstan on the path to a post-communist non-democracy.